Synergistic Response of Rifampicin with Hydroperoxides on Mycobacterium: A Mechanistic Study - Patel, Yesha S.; Mehra, Sarika (Frontiers in Microbiology, 2017)
Prolonged chemotherapy as well as rapid development of antimicrobial resistance are two of the major concerns for treatment of mycobacterial infections. To enhance the effectiveness of current drug regimens, search for compounds having synergistic interaction with anti-mycobacterial drugs has become indispensable. Here, we have investigated the intervention by oxidative stress, a major factor in mycobacterial pathogenesis, in combination with Rifampicin (RIF), a first-line drug used against Mycobacterium tuberculosis. We have observed that a sub-inhibitory concentration of Cumene Hydroperoxide (CHP), a hydrophobic oxidant, synergistically reduced the Minimum Inhibitory Concentration (MIC) of RIF by four-fold, with a Fractional Inhibitory Concentration Index (FICI) of 0.45. Also, this interaction was found to be robust and synergistic against different strains of Mycobacterium smegmatis as well as on Mycobacterium bovis BCG, with FICI ranging from 0.3-0.6. Various physiological, biochemical and molecular parameters were explored to understand the mechanism of synergy. It was observed that increased membrane permeability owing to the presence of the oxidant, led to higher uptake of the drug. Moreover, downregulation of the hydroperoxide reductases by RIF, a transcriptional inhibitor, prevented quenching of the reactive oxygen species (ROS) produced in the presence of CHP. The lipid soluble reactive species triggered autocatalytic lipid peroxidation (LPO), observed here as extensive membrane damage eventually leading to growth inhibition. Furthermore, it was seen that in combination with hydrogen peroxide (H2O2), the effect was only additive, establishing LPO as a key aspect leading towards synergism. To conclude, this work suggests that targeting the bacterial membrane by a radical species can have a significant impact on the treatment of tuberculosis.